Methods & theories of art history - D'Alleva, Anne. (London : Laurence King Publishing, 2012)
Art historical theory is a forum of intense, often passionate debate. This book provides an accessible introduction to the range of critical theories used in analysing art. It covers a range of approaches, presenting individual arguments, controversies and divergent perspectives
Previous ed.: 2005.
Includes bibliographical references and index.
boek
Keywords: Art criticism; Art -- History -- Methodology